Correlation of Interleukin-8, Pediatric Logistic Organ Dysfunction score and factors associated with systemic inflammatory response after cardiopulmonary bypass in children who have undergone open-heart surgery - Ririe F Malisie; Antonius H Pudjiadi; Fathema D Rachmat; Jusuf Rachmat (Indonesian Pediatric Society, 2010)
Background Cardiopulmonary bypass (CPB) provides a complex set of non-physiologic circumstances, induces systemic release of pro-inflammatory cytokines and initiates systemic inflammatory response. IL-8 is an important activator of neutrophil with chemotactic effect and are proposed to be major mediator of inflammation. The majority of general intensive care unit scoring system does not adequately address the specific characteristics of cardiac surgery patients. None of the study had been published the validation of PELOD score setting in pediatric cardiac intensive care unit (CICU).Objectives To evaluate the correlation between interleukin-8 (IL-8), Pediatric Logistic Organ Dysfunction (PELOD) score and factors associated with systemic inflammatory response after bypass (SIRAB) in children undergone cardiopulmonary bypass surgery.Methods A quasi-experimental study was conducted on children who have undergone cardiac surgery requiring CPB. There were 21 eligible children, two were excluded. Blood samples from mixed vein and coronary sinus were taken before, during and after surgery. The plasma level of IL-8 analyzed at 3 time points: baseline (before) CPB, at reperfusion period and 3 hours after aortic cross clamp-off. Cumulative organ dysfunctions were analyzed by PELOD score.Results The plasma level of IL-8 highly increase at the reperfusion period. IL-8 plasma level correlated with bypass-time (r > 0.49, p=0.003) and aortic cross clamp-time (r > 0.55, P=.014). Moderate association between age and PELOD score (r > 0.47, P=0.041). The correlations were significant between age and mechanical ventilation time support (r > 0.47, P=0.03), age and length of stay in CICU (r > 0.44, P=0.05). No correlation between IL-8 plasma level and PELOD score.Conclusion There was no correlation between IL-8 plasma level and PELOD score. IL-8 plasma level correlated with aortic cross clamp-time in children who undergo cardiopulmonary bypass surgery.